PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PERAN AUDIT INTERNAL DAN PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN - Sijabat, Murdhani Oloan; Virandi, R Rahmawan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of relationships or influences between variables. This article reviews the factors that affect the quality of financial statements, namely: competence of human resources, the role of internal audit and the application of accounting information systems a literature audit study. The purpose of writing this article is to build a hypothesis of influence between variables to be used in future research. The results of this literature review article are: the competence of human resources affects the quality of financial statements; the role of internal audit affects the quality of financial statements; and the application of accounting information systems affects the quality of financial statements.